Artificial Selection Finds New Hypotheses for the Mechanism of Wolbachia-Mediated Dengue Blocking in Mosquitoes - Ford, Suzanne A.; Albert, Istvan; Allen, Scott L.; Chenoweth, Stephen F.; Jones, Matthew; Koh, Cassandra; Sebastian, Aswathy; Sigle, Leah T.; McGraw, Elizabeth A. (Frontiers in Microbiology, 2020)
Wolbachia is an intracellular bacterium that blocks virus replication in insects and has been introduced into the mosquito, Aedes aegypti for the biocontrol of arboviruses including dengue, Zika and chikungunya. Despite ongoing research, the mechanism of Wolbachia-mediated virus blocking remains unclear. We recently used experimental evolution to reveal that Wolbachia-mediated dengue blocking could be selected upon in the A. aegypti host and showed evidence that strong levels of blocking could be maintained by natural selection. In this study, we investigate the genetic variation associated with blocking and use these analyses to generate testable hypotheses surrounding the mechanism of Wolbachia-mediated dengue blocking. From our results, we hypothesise that Wolbachia may block virus replication by increasing the regeneration rate of mosquito cells via the Notch signalling pathway. We also propose that Wolbachia modulates the host’s transcriptional pausing pathway either to prime the host’s anti-viral response or to directly inhibit viral replication.